Challenges in consolidating the evidences of robotic surgery for primary hepatobiliary malignancies - Chen, Po-Da; Wu, Yao-Ming (Laparoscopic Surgery, 2018)
We read “Long-term Oncologic Outcomes Following Robotic Liver Resections for Primary Hepatobiliary Malignancies: A Multicenter Study” with great interest. The report by Khan et al. provided a comprehensive analysis of various hepatobiliary cancers (1). Their data indicated that the robotic approach provided oncologic outcomes comparable to those reported previously with standard open and conventional laparoscopic approaches for primary liver and biliary malignancies. However, concerning the nature and different surgical demands of the various procedures, different liver and biliary malignancies shall be discussed in detail herein to clarify the role of the robotic platform.